Optimization and Analysis of a Low-Pressure Water Scrubbing Biogas Upgrading System via the Taguchi and Response Surface Methodology Approaches - Gad Reuben Mugagga; Isaiah Bosire Omosa; Thomas Thoruwa (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Biogas upgrading is essential in order to increase the calorific value and improve the quality of raw biogas. This present study aims at investigating the optimum performance of a near atmospheric pressure water scrubbing (NAPWS) system for biogas upgrading while using both the adsorption and absorption techniques. This was achieved through a two-stage process: namely, the Taguchi approach followed by the response surface methodology (RSM). The Taguchi orthogonal array design consisted of 27 runs where the raw biogas pressure (10 - 30 kPa), liquid flow rates (2.6 - 4.2 l/ min.) and variations of the steel wool height (0 - 45.72 cm) in the adsorption column were experimentally studied with respect to the methane (CH4) yield and removal efficiency of hydrogen sulfide (H2S) and carbon dioxide (CO2). From the experiments, the removal efficiency of hydrogen sulfide was greater than 87% with the average bio-methane content of 77.67%. During the second-stage, the analysis of variance (ANOVA) and the RSM were undertaken for optimization of the process parameters. The optimum bio-methane concentration of 84.71 (%v/v) CH4 and 13.31 (%v/v) CO2 was attained at gas pressure of 14kPa, liquid flow rate of 4.2 l/min., and steel wool height at 22.86cm obtained through numerical optimization. These results revealed that the utilization of the Taguchi and the RSM yielded to the best optimal system performance with the liquid flow rate as the most significant factor